An ethnobotanical survey of wild edible plants of Campania (Italy) - De Natale, Antonino; Menale, Bruno; Di Lecce, Serena; Pollio, Antonino (BORNH Bulletin of Regional Natural History, 2021)
A survey of the knowledge on edible wild plants in Campania (Italy) is presented. The checklist is based not only on literature data but also on unpublished results coming from archives of the authors. 639 records of alimentary uses related to 198 taxa are listed. Asteraceae, Lamiaceae, Brassicaceae and Rosaceae are the most represented families. The predominant biological forms are Hemycriptophytes, Terophytes and Phanerophytes. The parts of plant used as food mainly include leaves and aerial parts, followed by flowers, fruits and seeds, whereas roots and other underground parts are less frequently used. Many species are consumed in salads or soups and served in mixtures. The alimentary uses of most species are widespread in Campania, but the uses of 28 species are strictly linked to limited territories.